EFFECTIVENESS OF THREE INTRACANAL MEDICAMENTS AGAINST STAPHYLOCOCCUS AUREUS - Yunita Styaningrum; Arlina Nurhapsari; Denis Yusfa (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: Medikamen intrakanal used to remove remaining bacteria in the root canal after the instrumentation process, especially with some of the material between the infected root canal. The purpose of the medikamen intrakanal, among others, is reducing the number of bacteria, by preventing the growth of bacteria, eliminates exudate periapikal, prevent or restrain resorpsi root and prevent infected root canal system. The most influential of these bacteria i.e. Staphylococcus aureus. The purpose of this study was to determine the effectiveness of three intracanal medicament ingredients as anti-bacterial in Staphylococcus aureus.Method: The research, an experimental laboratory method carried out with a post test only control group design, was performed on Staphylococcus aureus bacteria that had been cultured and divided into 4 groups each given 1 mg zinc oxide paste, 1 mg antibiotic paste, 1 mg calcium hydroxide, and aquadest as negative control. Subsequently the results are seen from the zone of inhibition and kill zone which are measured by calliper and analyzed by One-way Annova followed by the Post-hoc LSD.Result: The result of On-way Anova test (p=0.000), showed there was a difference for using medicaments zinc oxyde, antibiotic paste, and calcium hydroxide towards Staphylococcus aureus. The post hoc LSD test showed there was a significant mean’sdefference of inhibition zone and kill zone (p-0.05) intergrups.Conclusion: there was an effect after using zinc oxyde, antibiotic paste, and calcium hydrxide as antibacterial on Staphylococcus aureus bacteria seen from inhibition zone and kill zone.